Interseeding Sorghum-Sudangrass into Perennial Cool-Season Western Wheatgrass Pasture - Keith Harmoney; John Guretzky (Kansas Agricultural Experiment Station Research Reports, 2022)
Conversion of pastureland into cropland has occurred at a rapid rate on the Great Plains. A reduction in total acreage of pastureland from this conversion has resulted in a decline of total numbers of beef cows in the same region. One method to mitigate the decline in cow numbers is to increase the carrying capacity of the remaining pastureland acres. To achieve this goal, a study was conducted to introduce warm-season annual grass species into perennial cool-season grass pastures to increase dry matter production during the mid-summer time period that perennial cool-season grasses would be most dormant. An increase in production during this time period could result in a significant overall increase in total land area production.
Keywords: crabgrass; forage yield; seedling density; teff; wheatgrass; cool season pasture